PENERAPAN PRINSIP CITIZEN’S CHARTER PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN GOWA - Renny Puteri Harapan Rani; Amir Imbaruddin; Muttaqin Muttaqin (Politeknik STIA LAN Makassar, 2018)
The purpose of this research is to know and analyze the application of citizen's charter principle to the Department of Investment and One Stop Service of Gowa Regency. The research method used is qualitative method. Data collection techniques through interviews, observation and document review. The research informants are 12 people, consisting of Head of Service 1 person, Head of Division 2 persons, Head of Section 4 person, and Service Licensing and Non Licensee 6 people. Processing and data analysis is a qualitative analysis conducted through five stages of data collection, data reduction, data display, data verification, and conclusion. The results show that DPM PTSP Gowa Regency has not fully applied the principle of citizen's charter as the theory of Oliver and Drewry, namely higher service standard, service openness, service information, non-discrimination service, service responsiveness, service grievances, as there is no cooperation with independent oversight agencies and charter signatures (directions) of service; there is no publication of the complete organizational structure with the names of authorized officials and the publication of the cost of services in a munual and online manner; no publication of performance target information and performance performance achievements online; does not yet have a regulation on guarantee of equal rights for the beneficiaries; the absence of requests for service recipient response by the employee for the services provided; the absence of cooperation with independent institutions as mediator between the DPM-PTSP Gowa District with the recipient of service in the event of no agreement on the settlement of complaints or complaints.